DIGITAL MARKETING AND YOUNG INVESTORS’ CONSUMER BEHAVIOR: THE ROLE OF INFLUENCER MARKETING AND CONTENT LITERACY IN FOSTERING TRUST AND CUSTOMER LOYALTY IN SECURITIES FIRMS - Novitry, Jundy; Nurjanah, Siti (International Journal of Cultural and Social Science, 2026)
Digital marketing has become a dominant channel influencing young investors’ behavior, particularly through the use of influencer marketing and educational content literacy. This study aims to analyze how influencer credibility, message clarity, and digital content literacy shape trust and loyalty toward securities companies. Using a qualitative descriptive approach, the research explores young investors’ perceptions through in-depth interviews and digital content analysis across social media platforms and investment applications. The findings reveal that credible influencers, relevant educational messages, and content aligned with the needs of beginner investors significantly enhance trust. Moreover, content literacy acts as a mediating factor that strengthens investment interest and long-term loyalty toward digital securities platforms. This study provides important implications for securities firms to optimize digital marketing strategies by integrating educational content and collaborating with trustworthy influencers to build sustainable relationships with young investors.